Early neonatal sepsis in COVID-19 era - A. L. Karpova; A. V. Mostovoi; E. А. Dudkina; O. V. Avdei; N. Yu. Karpov (Акушерство, гинекология и репродукция, 2023)
Introduction. Early-onset neonatal sepsis (EONS) remains the leading cause of serious mobility and mortality worldwide. At the present time, the impact of the COVID-19 pandemic on the incidence of other infections is of particular interest. Aim: to conduct a comparative analysis of the features of the course of EONS in newborns before the COVID-19 pandemic (2018) and during the COVID-19 pandemic (2021). Materials and Мethods. A retrospective cohort single-center continuous study included 73 newborns born and hospitalized in the Regional Kaluga Perinatal Center (PC) based on Kaluga Regional Clinical Hospital. The data for the period of stay in the PC from January to October 2018 and the same period in 2021 were analyzed and compared. Newborns were divided into two groups: group 1 (n = 26) – in 2018, and group 2 (n = 47) – in 2021. The following parameters of EONS severity were selected: the need for the use of norepinephrine, surfactant and fresh-frozen plasma (FFP). Results. The incidence of EONS in 2021 (n = 47) was significantly higher than in 2018 (n = 26): odds ratio (OR) = 3.27; 95 % confidence interval (CI) = 1.57–6.40; p = 0,001. Gestational age and Apgar score at the 1st and 5th minutes were significantly higher in group 1 than in group 2: 36.2 [33.3; 38.0] weeks vs. 33.3 [28.5; 36.1] weeks (p = 0.016); 7.0 [5.0; 7.0] vs. 5.0 [3.0; 7.0] (p = 0.019) and 9.0 [6.8; 8.0] vs. 6.0 [5.0; 8.0] (p = 0.012), respectively. Newborns with EONS in 2021 compared with 2018 showed a significant increase in norepinephrine administration of (42/47 vs. 16/26 newborns, respectively; OR = 5.25; 95 % CI = 1.58–17.44; p = 0.007), FFP transfusions (47/47 vs. 19/26 newborns, respectively; OR = 36.54; 95 % CI = 2.05–649.84; p < 0.001) and surfactant therapy (32/47 vs. 7/26 newborns, respectively; OR = 5.79; 95 % CI = 2.04–16.45; p = 0.001). Mortality among patients with EONS in 2021 compared to 2018 was significantly higher: 13/47 (21.3 %) vs. 2/26 (7.7 %) newborns, respectively (OR = 9.56; 95 % CI = 1.22–74.96; p = 0.014). Conclusion. Among the newborns of the Kaluga region there is a significant rise in the incidence and mortality of EONS on the background of the COVID-19 pandemic. In 2021 there is a significant increase in the need for surfactant administration, use of vasopressors, and transfusion of FFP in infants with EONS.